(untitled) (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
The purpose of this study was to identify and analyze the factors that caused the performance of the Staff of the 600th Infantry Raider Battalion/Modang Kodam VI/Mulawarman Balikpapan staff to improve, and to identify and analyze efforts to improve the performance of the 600th Infantry Raider Battalion staff. /Modang Kodam VI/ Mulawarman Balikpapan, East Kalimantan. This research uses qualitative research with data collection techniques such as interviews, document analysis, and observation. The data analysis method used by the author is using the Miles and Huberman method. The results showed that the factors causing the performance of the Staff of the Personnel Section in the Personnel Division of the 600th Raider Infantry Battalion/Modang Kodam VI/Mulawarman still need to be improved in terms of the need for training of soldiers in the provision, education, use, maintenance, and separation so that it affects the performance of soldiers, still there are some staff who have not had an undergraduate education and managerial and computer skills still need to be added, but the current condition is that soldiers actually have the requirements to carry out education but the quota given to attend education is very limited, the number of staff in the personnel department is inadequate so they still cannot meet DSP. Efforts to improve the performance of the Staff of the Personnel Division of the 600th Infantry Raider Battalion/Modang Kodam VI/Mulawarman include: (1) Effort-1: Improving the pattern of personnel staff development, reward and punishment, application of the merit system and improving the pattern of care for the Staff of the Personnel Division. (2) Effort-2: Increasing the leadership commitment to the education of special qualifications for personnel staff. (3) Effort-3: Arranging the placement of the Personnel Division Staff with the aim of fulfilling the DSP for personnel staff in all TNI AD work units.